An exploratory study of how paediatric student nurses who are religious respond to the religious needs as an aspect of spirituality of the children and their families in hospitals - Alimi, Taiwo (2011)
This study aims to explore the attitudes of pre-registration religious student nurse to identify whether their religious identity shapes their nursing practice, specifically in the provision of spiritual care. As identified in the literature, it is important to meet spiritual needs of patients as it encompasses holistic care. There were vast amounts of research looking into factors that affect the practice of spiritual care and others exploring the patients’ perspective of spiritual care. However there are limited research exploring whether religious student nurses provide spiritual care in a religious way, which justify this study. A qualitative exploratory approach was utilised with the use of semi-structured interviews. This allowed the collection of in-depth data from six pre-registration student nurses who claimed to be religious was gathered and analysed. The analysis process yielded three themes: nurses identity and how spiritual and/or religious needs are met, understanding of spirituality and religion and spirituality is conflated with religion. It was found that those that have a religious explanation of spirituality considered to meeting children’s spiritual or religious needs whether or not the child was religious. Interestingly, those who claimed to be religious suspended their religious beliefs whilst practising nursing especially in the area of meeting spiritual needs, which may suggest negative connotations to religion. However, religious needs were seen as an aspect of spiritual care when taking caring of children with life limiting illness or in palliative care, but was generally seen as the role of the chaplaincy. It appears that spirituality and religion are two confusing concepts when combined together, but the only link between them was in palliative care. The ideas and opinions of the student nurses suggest that personal perceptions have a role in influencing nursing practice. This research could be potentially aid in shaping nursing education in spirituality and religion in the future.